Influence of limiting factors on biomass and lipid productivities of axenic Chlorella vulgaris in photobioreactor under chemostat cultivation. (July 2016) - Cho, Dae-Hyun; Ramanan, Rishiram; Heo, Jina; Shin, Dong-Sik; Oh, Hee-Mock; Kim, Hee-Sik
Highlights: Study of limiting factors affecting algal biomass and lipid productivities in chemostat. Inorganic carbon, phosphorus and light intensity are major limiting factors in PBR. Optimized limiting factor and dilution rate yielded higher (>10 times) productivity. Abstract: The understanding of process parameters and limiting conditions on microalgal biomass and lipid productivities is scarce especially in chemostat cultivation. In this study, the factors limiting growth of axenic Chlorella vulgaris OW-01 in cylindrical photobioreactor under chemostat cultivation were overcome in two phases. Physiological and physicochemical analyses determined inorganic carbon, phosphorous and light intensity as major limiting factors. Their effect on system productivity was ascertained and optimized in the first phase resulting in maximum biomass and lipid productivities of 538 and 128 (mg/L/d), respectively. In the second phase, the effect of dilution rate was evaluated under optimized conditions. The biomass and lipid productivities in this phase reached to 1013 and 270 (mg/L/d), respectively at a dilution rate of 0.75 d −1, yielding >10-fold cumulative increase in productivities. The study demonstrates addressing resource limitations by constant monitoring and optimization of chemostat cultivation to achieve high biomass and lipid productivities in photobioreactors.